The effect of fine bubble aeration intensity on membrane bioreactor sludge characteristics and fouling. (1st June 2015) - De Temmerman, L.; Maere, T.; Temmink, H.; Zwijnenburg, A.; Nopens, I.
Abstract: While most membrane bioreactor (MBR) research focuses on improving membrane filtration through air scour, backwashing and chemical cleaning to physically counteract fouling, relatively few studies have dealt with fouling prevention, e.g. minimizing the impact of operational settings that negatively impact sludge filterability. To evaluate the importance of those settings, the effects of bioreactor aeration intensity variations on membrane fouling have been studied in a lab-scale MBR setup while simultaneously monitoring a unique set of key sludge parameters. In particular, this paper focuses on the impact of shear dynamics resulting from fine air bubbles on the activated sludge quality and flocculation state, impacting membrane fouling. When augmenting the fine bubble aeration intensity both the total and irreversible fouling rate increased. Major indications for sludge filterability deterioration were found to be a shift in the particle size distribution (PSD) in the 3–300 μm range towards smaller sludge flocs, and increasing concentrations of submicron particles (10–1000 nm), soluble microbial products and biopolymers. When lowering the aeration intensity, both the sludge characteristics and fouling either went back to background values or stabilized, respectively indicating a temporary or more permanent effect, with or without time delay. The shift in PSD to smaller flocs and fragments likely increased the total fouling through the formation of a less permeable cake layer, while high concentrations of submicron particles were likely causing increased irreversible fouling through pore blocking. The insights from the performed fouling experiments can be used to optimize system operation with respect to influent dynamics. Highlights: Fine bubble aeration dynamics impact the activated sludge filterability. Loose supramicron sized flocs become more compact through high aeration. Submicron particle concentration and SMP are related to fine bubble aeration dynamics. Immediate effect on total, versus delayed effect on irreversible membrane fouling. Better design/operation improves flocculation and prevents negative effects.